2011
DOI: 10.1038/cdd.2011.20
|View full text |Cite
|
Sign up to set email alerts
|

The p53 target Wig-1: a regulator of mRNA stability and stem cell fate?

Abstract: Wig-1 is a transcriptional target of the tumor suppressor p53 and encodes an unusual zinc-finger protein involved in posttranscriptional gene regulation. Wig-1 is expressed in all cell types investigated so far, with the highest levels in the brain, and is enriched in stem cells as compared with more differentiated cells of the same lineage. Wig-1 binds to both long double-stranded (ds) RNA and short microRNA-like dsRNA. We have shown that Wig-1 acts in a positive feedback loop that stabilizes p53 mRNA through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 65 publications
1
29
0
Order By: Relevance
“…WIG-1 as a bona fide p53 target gene has been confirmed by a number of studies [15,17,19] and is further supported by microarray data showing WIG-1 upregulation after p53 activation by the small molecule RITA [20]. However, it is clear that p53 is not the only transcription factor that regulates WIG-1 expression, as WIG-1 is expressed at robust levels also in cells lacking p53 [21]. Our results also suggested that zinc could upregulate the expression of WIG-1 not by regulating the p53.…”
Section: Discussionmentioning
confidence: 74%
“…WIG-1 as a bona fide p53 target gene has been confirmed by a number of studies [15,17,19] and is further supported by microarray data showing WIG-1 upregulation after p53 activation by the small molecule RITA [20]. However, it is clear that p53 is not the only transcription factor that regulates WIG-1 expression, as WIG-1 is expressed at robust levels also in cells lacking p53 [21]. Our results also suggested that zinc could upregulate the expression of WIG-1 not by regulating the p53.…”
Section: Discussionmentioning
confidence: 74%
“…Later studies demonstrated the ability of ZMAT3 to bind to double stranded RNA, besides DNA, and is thought to play a role similar to that of miRNA [87-89]. Interestingly, its expression was found to be highest in the brain [89].…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in p53 increases cell reprogramming efficacy and facilitates induced pluripotent stem cell (iPSC) generation [137]. p53 may also act to regulate stem cell fate by targeting a variety of factors, such as Wig1, a transcriptional p53 target encoding a zinc-finger protein involved in post-transcriptional gene regulation, and is found to be highly expressed in stem cells [151]. In tumors, mut p53 acquires GOF processes to influence stemness as observed in its ability to stimulate iPSC formation while augmenting the malignant potential of reprogrammed cells [20].…”
Section: P53 and Stem Cellsmentioning
confidence: 99%